Infortuni a rischio di malattie a trasmissione ematica nel personale ostetrico: analisi di una casistica ospedaliera / Accidents with risk of blood-borne infections in obstetricians: analysis of a hospital case record - Sacchi, M.; Daglio, M.; Feletti, et al., T. (La Medicina del Lavoro, 2007)
Lo studio esamina le modalità di esposizione accidentale a fluidi corporei nel personale ostetrico della Fondazione IRCCS Policlinico San Matteo di Pavia dal 1994 al 2005. Dai registri di esposizione risulta che il fenomeno infortunistico riguarda soprattutto gli operatori strutturati con meno di 5 anni di anzianità lavorativa, principalmente in forma di puntura con ago o con altro presidio tagliente contaminato, oppure come schizzo di materiale biologico, spesso in assenza di dispositivi di protezione individuale. Seppure in alcuni casi il contatto fosse avvenuto con fluidi biologici provenienti da fonti infette, non è stato documentato alcun caso di sieroconversione nel personale coinvolto. Al fine di ridurre il rischio globale di infezione da patogeni a trasmissione ematica nella categoria di operatori analizzata, si sottolinea la necessità di attuazione da parte delle aziende sanitarie di una strategia che comprenda la disponibilità di adeguati dispositivi di protezione individuale, la formazione, la diffusione e il rispetto delle norme generali di isolamento, l’utilizzazione di presidi forniti di dispositivi di sicurezza.Accidents with risk of blood-borne infections in obstetricians: analysis of a hospital case recordBackground: Health care workers (HCW) are at high risk of accidental contact with biological fluids. In spite of extensive recommendations concerning HCW, accidents continue to be frequent and seem to be related to specific factors. Objectives: To evaluate the factors influencing risk of blood-borne infections in a particular category of HCW - obstetricians, and obtain information useful for prevention guidelines. Methods: Data were obtained from the exposure registers of nursing and of the Emergency Ward staff, where HCW first report after accidental contact with biological fluids. Results: Accidents with risk of blood-borne diseases were more frequent in obstetricians with lower job seniority. They usually occurred between 8 a.m. and 4 p.m., in the patient’s room. The hands and face (particularly the eyes) were the body parts more often involved. In almost half of the accidents, the worker was not wearing any personal protective device. Although some contacts were with infected blood, no seroconversion occurred. Conclusions: Obstetricians are at high risk of contact with biological fluids. Prevention requires a global strategy including the availability of protective and safety devices, as well as worker education, especially concerning the use of such devices, the application of the universal rules of prevention and the improvement of risk awareness. An adequate post-exposure management of accidents in also required.